Refugee protection: A Guide to International Refugee Law (2001)
The Handbook has therefore a twofold purpose: to inform parliamentarians about the founding principles and challenges of international refugee law and also to mobilise them, as policy makers, in the implementation of the law for securing adequate protection of refugees